Blue-chip Black : race, class, and status in the new Black middle class - Lacy, Karyn R., 1965- (ACLS Humanities E-Book., 2007)
Explores middle-class blacks who live in suburbs where poor blacks are not present. This book examines the sense of identity that individuals in these groups craft to manage their interactions with lower-class blacks, middle-class whites, and other middle-class blacks as they seek to reap the benefits of their middle-class status.